Method development and validation: quantitation of telmisartan bulk drug and its tablet formulation by 1H NMR spectroscopy. (17th January 2017) - Jadeja, Yashwantsinh; Chomal, Bhagyawanti; Patel, Madhavi; Jebaliya, Hetal; Khunt, Ranjan; Shah, Anamik
Abstract : The quantitative NMR (qNMR) spectroscopy is nowadays a new tool for the determination of pharmaceutical potent biologically active molecules in bulk drug and its tablet formulation than the other analytical techniques. Herein, qNMR method was developed for an anti‐hypertensive drug, telmisartan in bulk drug and its tablet formulation. The precise method was developed by using malononitrile as an internal standard. The methylene signal of telmisartan appeared at δ = 5.46 ppm (singlet) relative to the signal of malononitrile at δ = 3.59 ppm (singlet) in CDCl3, as an NMR solvent. The development and validation of the method were carried out as per International Conference on Harmonization guidelines. The method was found to be linear (r 2  = 0.9999) for 0.5 to 3.5 mg/ml in the drug concentration range. The relative standard deviation for accuracy and precession was not more than 2.0%. The sensitivity of the method was carried out by limit of detection and a limit of quantification, at 0.05 and 0.2 mg/ml, respectively, concentration. The robustness of the method was studied by changing parameters as well as different solvent manufacturer company. The result shows that method was accurately developed for quantification of telmisartan in pharmaceutical dosage form. The developed method by 1 H NMR spectroscopy is comparatively easy and more precise with respect to the other analytical tools. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Telmisartan bulk drug and its tablet formulation are quantitated by 1 H NMR spectroscopy using malononitrile. The development and validation of the method were carried out as per International Conference on Harmonization guidelines. The sensitivity of the method was carried out and, at 0.05 (LOD) and 0.2 (LOQ) mg/ml concentration. More precise qNMR method is developed with respect to the other analytical tools.